Transient Processes in a Binary System with a White Dwarf - D. A. Kononov; D. V. Bisikalo; V. B. Puzin; A. G. Zhilkin (Acta Polytechnica CTU Proceedings)
Using the results of 3D gas dynamic numerical simulations we propose a mechanism that can explain the quiescent multihumped shape of light curves of WZ Sge short-period cataclysmic variable stars. Analysis of the obtained solutions shows that in the modeled system an accretion disk forms. In the outer regions of the disk four shock waves occur: two arms of the spiral tidal shock; “hot line”, a shock wave caused by the interaction of the circum-disk halo and the stream from the inner Lagrangian point; and the bow-shock forming due to the supersonic motion of the accretor and disk in the gas of the circum-binary envelope. In addition, in our solutions we observe a spiral precessional density wave in the disk. This wave propagates from inside the disk down to its outer regions and almost rests in the laboratory frame in one orbital period. As a results every next orbital period each shock wave passes through the outer part of the density wave. Supplying these shocks with extra-density the precessional density wave amplifies them, which leads to enhanced energy release at each shock and may be observed as a brightening (or hump) in the light curve. Since the velocity of the retrograde precession is a little lower that the orbital velocity of the system, the same shock wave at every next orbital cycle interacts with the density wave later than at the previous cycle. This causes the observed shift of the humps over binary phases. The number of the shock waves, interacting with the density wave determines the largest number of humps that may be observed in one orbital period of a WZ Sge type star.